Emerging Trends in the Application of Nanosuspension-Based Biomaterials for Anticancer Drug Delivery - Aldeeb MME; Wilar G; Suhandi C; Mohammed AFA; Mahmoud SA; Elamin KM; Wathoni N (International Journal of Nanomedicine)
Mohamed Mahmud E Aldeeb,1– 3 Gofarana Wilar,4 Cecep Suhandi,1,2 Ahmed Fouad Abdelwahab Mohammed,5 Safwat A Mahmoud,6 Khaled M Elamin,7 Nasrul Wathoni2 1Doctoral Program of Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, 45363, Indonesia; 2Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, 45363, Indonesia; 3Department of Pharmaceutics, Faculty of Pharmacy, Elmergib University, Alkhoms, 40414, Libya; 4Department of Pharmacology and Clinical Pharmacy, Faculty of, Universitas PadjadjaranPharmacy, Jatinangor, 45363, Indonesia; 5Department of Pharmaceutics, Faculty of Pharmacy, Minia University, Minia, 61517, Egypt; 6Center for Scientific Research and Entrepreneurship, Northern Border University, Arar, 73213, Saudi Arabia; 7Graduate School of Pharmaceutical Sciences, Kumamoto University, Kumamoto, 862-0973, JapanCorrespondence: Nasrul Wathoni, Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, 45363, Indonesia, Tel +62-22-842-888-888, Email nasrul@unpad.ac.idAbstract: The treatment of cancer remains a formidable challenge, largely due to the difficulty in achieving efficient co-delivery of chemotherapeutic and immunotherapeutic agents to specific tumor sites. Nanosuspension-based biomaterial drug delivery systems for anti-cancer (NBDDSC) have emerged as promising platforms for enhancing drug solubility, stability, and targeted delivery. These systems can be categorized into natural polymer-based, synthetic polymer-based, and hybrid nanosuspensions, each offering distinct advantages in biocompatibility, drug loading, and controlled release. However, the majority of existing NBDDSC rely on synthetic materials that function primarily as excipients, offering no intrinsic therapeutic value. These materials often require intricate manufacturing processes, which can result in issues with batch consistency, reduced stability, and diminished therapeutic efficacy. Additionally, the potential side effects associated with synthetic components further underscore the limitations of these systems. This review explores various preparation methods for nanosuspensions, including antisolvent precipitation, high pressure homogenization, and ultrasonication, highlighting their impact on particle size, drug encapsulation, and stability. Furthermore, the targeted applications of these nanosuspensions in treating of cancers such as glioma is discussed to emphasize their potential clinical relevance. By addressing current limitations, this review underscores the critical importance of simpler, safer, and clinically translatable NBDDSC in advancing cancer therapy.Keywords: nanosuspension, cancer, biomaterials, tumor, NBDDSC